Improving the Quality of the Software through Aspects - De Castro Bertagnolli, Silvia (2003)
Many software projects have failed because they are based on a poor set of quality attributes. Moreover, the growing use of these requirements in the software has made researchers focus their attention on methodologies and processes to deal with it. We propose a well-defined model intended to guide the developer through the software development lifecycle. Its goal is to determine a systematic way to elicit and model non-functional requirements, and establish a practice manner to improve the software quality. The FRIDA model is founded on the aspect-oriented software development. In this paradigm, the aspect is a complementary manner to describe the non-functional features related to any application. In our approach, the crosscutting nature of the requirements is considered during all software lifecycle. Furthermore, each NFR is represented with one or more aspects and FRs are restricted to classes hierarchies